KURASI DIGITAL SASTRA SIBER: PERSPEKTIF SASTRA KONVENSIONAL: Array - Meilisa Arismaya Wanti (Arsip Nasional Republik Indonesia, 2020)
The last two decades signified the shift in the period of literary development. The emergence of various literary works that developed in the internet era succeeded in breaking the order of conventional literary publications which originally needed a layered process to be able to reach the readers. The rapid development of cyber literature produced many new literary works. Even though its quality is still being debated, it cannot eliminate its entity as a literary work and its role as a cultural product that must be preserved. That becomes a special aspect in this study, which aims to give consideration regarding preservation of cyber literary works in the form of digital curation of literature. This study considers the digital curation process of literature as the use of digital curation systems in the field of archives. This study uses descriptive qualitative methods to identify the urgency of digital curation of cyber literature. Furthermore, this analysis can be considered to produce collaboration between fields of literary, archival, and library science.